Cognitive maturation in preterm and term born adolescents. Issue 4 (6th August 2007) - Allin, M; Walshe, M; Fern, A; Nosarti, C; Cuddy, M; Rifkin, L; Murray, R; Rushe, T; Wyatt, J
Abstract : Background: Adolescence is a critical period of brain structural reorganisation and maturation of cognitive abilities. This relatively late developmental reorganisation may be altered in individuals who were born preterm. Methods: We carried out longitudinal neuropsychological testing in 94 very preterm individuals (VPT; before 33 weeks' gestation) and 44 term born individuals at mean ages of 15.3 years (adolescence) and 19.5 years (young adulthood). Results: Full scale, verbal and performance IQ and phonological verbal fluency were significantly lower in the VPT group than the term group at both ages. Repeated measures ANOVA showed only one group by time point interaction for semantic verbal fluency (F = 10.25; df = 107; p = 0.002). Paired-sample t tests showed that semantic verbal fluency increased significantly in the term group over adolescence (t = −5.10; df = 42; p<0.001), but did not increase in the VPT group (t = 0.141; df = 69; p = 0.889). For verbal IQ, there was a significant interaction between time point and sex (F = 4.48; df = 1; p = 0.036) with paired-sample t tests showing that verbal IQ decreased in males between adolescence and adulthood (t = 3.35; df = 71; p = 0.001), but did not change significantly in females (t = 0.20; df = 52; p = 0.845). Conclusion: Decrements of intellectual functioning in VPT individuals persist into adulthood. Additionally, there is a deficit in the adolescent maturation of semantic verbal fluency in individuals born VPT.